Differences in Applied Redox Potential on Cathodes Enrich for Diverse Electrochemically Active Microbial Isolates From a Marine Sediment - Lam, Bonita R.; Barr, Casey R.; Rowe, Annette R.; Nealson, Kenneth H. (Frontiers in Microbiology, 2019)
The diversity of microbially mediated redox processes that occur in marine sediments is likely underestimated, especially with respect to the metabolisms that involve solid substrate electron donors or acceptors. Though electrochemical studies that utilize poised potential electrodes as a surrogate for solid substrate or mineral interactions have shed some much needed light on these areas, these studies have traditionally been limited to one redox potential or metabolic condition. This work seeks to uncover the diversity of microbes capable of accepting cathodic electrons from a marine sediment utilizing a range of redox potentials, by coupling electrochemical enrichment approaches to microbial cultivation and isolation techniques. Five lab-scale three-electrode electrochemical systems were constructed, using electrodes that were initially incubated in marine sediment at cathodic or electron-donating voltages (five redox potentials between −400 and −750 mV versus Ag/AgCl) as energy sources for enrichment. Electron uptake was monitored in the laboratory bioreactors and linked to the reduction of supplied terminal electron acceptors (nitrate or sulfate). Enriched communities exhibited differences in community structure dependent on poised redox potential and terminal electron acceptor used. Further cultivation of microbes was conducted using media with reduced iron (Fe0, FeCl2) and sulfur (S0) compounds as electron donors, resulting in the isolation of six electrochemically active strains. The isolates belong to the genera Vallitalea of the Clostridia, Arcobacter of the Epsilonproteobacteria, Desulfovibrio of the Deltaproteobacteria, and Vibrio and Marinobacter of the Gammaproteobacteria. Electrochemical characterization of the isolates with cyclic voltammetry yielded a wide range of midpoint potentials (99.20 to −389.1 mV versus Ag/AgCl), indicating diverse metabolic pathways likely support the observed electron uptake. Our work demonstrates culturing under various electrochemical and geochemical regimes allows for enhanced cultivation of diverse cathode-oxidizing microbes from one environmental system. Understanding the mechanisms of solid substrate oxidation from environmental microbes will further elucidation of the ecological relevance of these electron transfer interactions with implications for microbe-electrode technologies.